Expansion and Fragmentation: Internationalization, Political Change and the Transformation of the Nation-State - Kees van Kersbergen, Robert H. Lieshout, and Grahame Lock (Amsterdam University Press, 2014)
We live, as is often remarked, in a fast-changing world. Some of the changes to which we are witness - and which are of practical concern to us all - lie in the political sphere. For instance, advanced societies are marked, among other things, by complex shifts in the power and competence of the nation state. It is said that state and society are becoming increasingly interwoven, leading to a 'politicization of society' and a 'socialization of the state'. This implies that the tasks and responsibilities of the nation state are in continuous expansion. Yet a process of 'individualization' and 'fragmentation' of political and social life also seems to be taking place; to this must be added a redistribution of some of the capacities of the nation state to regional or local levels as well as to 'intermediate bodies'. In the opposite direction, however, other developments, like internationalization, including the emergence of new regulatory systems at international level, are generating what are called 'transnational' networks. These appear to be gaining control of ever more aspects of social and political existence. As a result of these developments, political decision-making is becoming opaque, and the mechanisms of democratic control - which have traditionally operated in the framework of the nation state - seem to be in a process of erosion. At the same time the scope and the character of political participation are being modified: new networks are emerging as links between the various decision-making levels, while support for 'national society' is falling, and the efficacy of national governance structures is declining. Thus expansion, individualization, localization, internationalization and fragmentation have all become keywords summarizing the phenomenon of political change as it now affects advanced societies.